2007
DOI: 10.1007/s10886-006-9236-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Behavioral Activity of Secondary Metabolites in the Confused Flour Beetle, Tribolium confusum

Abstract: Several previous studies have addressed pheromone communication in various flour beetles (Coleoptera: Tenebrionidae), including the confused flour beetle, Tribolium confusum (du Val). Different stereoisomers of 4,8-dimethyldecanal (DMD) were reported as the only components of an aggregation pheromone, but the behavioral activity of DMD is low. In the present study, additional previously reported secondary metabolites (benzoquinones and hydrocarbons) were tested for electrophysiological activity (EAG) with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 31 publications
2
62
1
4
Order By: Relevance
“…We showed significant repellence and determined that at the highest density (1,250 beetles in 10 g of flour), the beetles consistently emitted volatiles that were repellant in our assays. This may be correlated with the release of very high levels of the benzoquinones that are repellant to larvae and adults at high concentrations (Mondal, 1985;Verheggen et al, 2007) or to the reduced release of the aggregation pheromone DMD (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…We showed significant repellence and determined that at the highest density (1,250 beetles in 10 g of flour), the beetles consistently emitted volatiles that were repellant in our assays. This may be correlated with the release of very high levels of the benzoquinones that are repellant to larvae and adults at high concentrations (Mondal, 1985;Verheggen et al, 2007) or to the reduced release of the aggregation pheromone DMD (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…The production of (−)-β-caryophyllene by females of H. axyridis was confirmed in the present study by volatile collection and subsequent GC-MS analysis (data not shown). Whereas cases of aggregation pheromone release by one sex only are common in the Coleoptera (e.g., Verheggen et al 2007), the use of a chemical commonly found in the headspace of various plants as an aggregation pheromone might be inappropriate. One might put forth the assumption that lady beetles have different antennal sensitivity to (−)-β-caryophyllene according to the season, being more sensitive during winter conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The tip of the recording electrode was bowlshaped, and half of the last distal antennal segment was immersed into the saline solution. This setup was previously shown to produce elegant results in the study of the olfactory responses of the confused flour beetle, Tribolium confusum Du Val (Coleoptera: Tenebrionidae), to its aggregation pheromone (Verheggen et al 2007). The DC potential was recorded on a computer (Auto Spike v. 3.0) by using an amplifier (IDAC-4, Syntech®, Hilversum, The Netherlands) with 100-fold amplification.…”
Section: Electrophysiology (Eag)mentioning
confidence: 99%
“…Furthermore, males fed low-nutrition diet showed a threefold reduction in their daily DMD production (Ming and Lewis 2010), suggesting that females could use DMD as a condition-dependent indicator of male quality. However, females were not preferentially attracted to filter paper disks carrying odors from high-nutrition males (Ming and Lewis 2010), and existing evidence for sexual dimorphism in response to synthetic DMD is conflicting (Levinson and Mori 1983;Obeng-Ofori and Coaker 1990;Verheggen et al 2007). In the former and numerous other studies, males' total olfactory cues have been collected onto filter paper disks over many days, thus reflecting a composite and time-integrated chemical profile.…”
Section: Evidence For Pre-mating Female Assessment Of Long-range Malementioning
confidence: 99%
“…Few hydrocarbons have been found in several Tribolium species (Markarian et al 1978;Lockey 1978), and some (e.g., 1-pentadecene, 1-tetradecene, and 1-hexadecene) have been assigned pheromonal function for T. confusum (Verheggen et al 2007). These and potentially other still unidentified compounds might be responsible for male attractiveness together with DMD, or they may act sequentially at different stages of intersexual interactions.…”
Section: Evidence For Pre-mating Female Assessment Of Long-range Malementioning
confidence: 99%